2011
DOI: 10.1007/s10753-011-9299-3
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Suppresses Metastasis in Rat Hepatocellular Carcinoma through Decreasing Interleukin-6 and Hepatocyte Growth Factor Expression

Abstract: Metastasis remains one of the major challenges before hepatocellular carcinoma (HCC) is finally conquered. Estrogen has recently emerged as a protective factor in the development and progression of HCC, but whether and how it reduces metastasis of HCC remain to be elucidated. We conducted an in vivo highly metastatic rat HCC model in female Sprague-Dawley rats induced by diethylnitrosamine and N-nitrosomorpholine to examine the effects of estrogen on HCC metastasis. Moreover, female rats were randomly distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…Previous studies reported that estrogen reduces IL-6 production and therefore inhibits carcinogenesis and osteoporosis [41, 4951]. More importantly, estrogen may have an anti-inflammatory effect due to inhibition of NF-κB activation [52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that estrogen reduces IL-6 production and therefore inhibits carcinogenesis and osteoporosis [41, 4951]. More importantly, estrogen may have an anti-inflammatory effect due to inhibition of NF-κB activation [52].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that isRNA induces the synthesis of type 1 interferon but not pro-inflammatory cytokines is important for the evaluation of the inducer as a potential adjuvant, since the inflammatory microenvironment contributes to the development of hepatic fibrosis, cirrhosis, carcinogenesis, and eventually tumor metastasis [29,30]. Pro-inflammatory cytokines TNF-α and IL-6 were found to be the main mediators of HCC invasion [31]. Similar results were reported by other groups [26,32-34]; these data show that 6–7 hours after injection into mice of different types of immunostimulatory siRNA with mixed functions complexed with cationic liposomes, a systemic immune response was induced, accompanied by IFN-α, IL (interleukin)-6, and/or IFN-γ production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that ERs are highly expressed in neoplastic liver, while increased ARs are associated with poor HCC prognosis . Recently, physiological doses of estrogen, no matter endogenous or exogenous, are demonstrated to suppress metastasis of HCC through modulation of inflammatory tumor microenvironment by suppression of HGF and IL‐6 production . Estrogen attenuates HCC progression in vitro and in vivo, and this may contribute to the gender differences in HCC behavior.…”
Section: Noncellular Component Involving Hcc Metastasismentioning
confidence: 99%